Lessons from Enterprise Reforms in China and Vietnam Can Stylized Necessary Conditions for the Sustainability of Socialist-Oriented Economic Strategies Be Identified? - GABRIELE, Alberto (Theoretical and Practical Research in Economic Fields; Vol 7 No 1 (2016): TPREF, Volume VII, Issue 1(13), Summer 2016DO - 10.14505/tpref.v7.1(13).05, 2016)
This paper surveys a few key features of socialist-oriented economic (SOE) reforms in China and Vietnam, focusing particularly on the evolution of ownership structures and on the relative weight of market regulatory mechanisms, and discusses their general implications for socialist development. It tentatively concludes that some broad principles informing and constraining any feasible socialist-oriented economic strategy can indeed be identified.